Assessing needs and opportunities for a technology business incubator serving the information technology industry in Nepal - Shrestha, Ritesh; Igel, Barbara; Islam, Nazrul; Donyaprueth Krairit; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2005)
There has been a fast growth of the information technology in the recent past and it constitutes a major opportunity for the economic development in a country. Information and communication technologies and electronic commerce can be expected to drive the trade component of economic growth for many years to come, and Nepal can not possibly afford to be left out. Nepal needs to seriously evaluate its position concerning the emergence of Information Economy worldwide. The major focus of this study is to assess the needs for a technology business incubator to improve the entrepreneurial world in Nepal, focusing on the information technology industry. Benchmarking with the various technology business incubators in different regions and their best practices, the opportunities that exist for the establishment of a technology business incubator, considering the available supply sides, are also discussed. It has been found that the present state of the information technology in Nepal is still in its early growth stage. The IT industry and the entrepreneurial world have merely seen the threshold of a proper community and economic development through its implementation. It is apparent that a progressive step by step development program is essential. A gradual step of for this progress program can be classified into the following levels of development. 1. Business Awareness 2. Business and Technology Knowledge Transfer 3. Business Development Performance and Programs 4. Business Community Development A proper networking with all the possible supply sides with the new startup companies through a body is essential to achieve this goal. Since a technology business incubator appears to respond to these desires by serving a mechanism for various development services, later resulting in community and economic development of a country, it is high time now that Nepal's entrepreneurial world also need a technology business incubator to help them foster in a proper competitive business environment.
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Project (M.B.A.) - Asian Institute of Technology, 2005
Keywords: Business incubators -- Nepal; Information technology -- Nepal